Bi-based halide perovskites: Stability and opportunities in the photocatalytic approach for hydrogen evolution - Magdalena Miodyńska; Tomasz Klimczuk; Wojciech Lisowski; Adriana Zaleska-Medynska (Catalysis Communications, 2023)
In this study, we successfully prepared Bi-based single perovskites of the A3Bi2I9 type (A = Cs, Rb, MA, FA), and, for the first time, attempted to experimentally obtain double perovskites Cs2B'BiI6 type (B′ = Ag, Au, In, Cu). Despite the premises available in theoretical studies, our research has proven the impossibility of the existence of double perovskites of this type. Nevertheless, both types of obtained materials were subjected to detailed analysis of their physicochemical features and photocatalytic abilities in the hydrogen evolution reaction. This study proved the stability of the Cs3Bi2I9 in HI electrolyte compared to the methanolic solution, with this phenomenon resulting in almost 36 times higher photoactivity.